Efectos de la danza folclórica y urbana sobre el desarrollo motor en niños de grado preescolar del colegio Pablo VI en Bogotá (2019)
This research assessed the effects of an urban and folk-dance program on motor development in preschool children, which was implemented over eight weeks in 90-minute sessions on 44 children aged 4 to 7 (m x 5.64; of 0.68) at the Pablo VI District Educational Institution in Bogota. The study had a quantitative approach, descriptive scope and pre and posttest, with the comparison two experimental groups: ge1 (folk dance, n = 25) and GE2 (urban dance, n = 19). Size and weight were evaluated, and the TGMD-2 test was used to measure motor development. Statistical analysis was performed with spss software, version 25. The variables had normal distribution and their significance value was p < 0.05. The results obtained indicated the positive effects on motor skills evaluated from the intervention. An increase of about 50 % was evident in the manipulative component, and 31 % in the locomotive component. It is recommended to include dance in school academic programs as a means of stimulation and motor development of children.